Analisis Pembebanan Uang Pengganti Dalam Tindak Pidana Korupsi - Aisyah, Siti; Atikah Rahmi (UNES Law Review, 2023)
The criminal acts of corruption that have occurred so far have not only been detrimental to state finances, but also constitute a violation of the social and economic rights of society at large. Criminal acts of corruption which have occurred widely, have not only harmed state finances, but have also constituted violations of the social and economic rights of society at large, so that criminal acts of corruption need to be classified as crimes whose eradication must be carried out in an extraordinary manner. The research objective used in writing this journal is normative juridical research or commonly called normative legal research. Normative juridical research is a research method used to determine the legal norms contained in statutory regulations. In Indonesia, corruption is a collaboration between actors in the public sector and the private sector. This situation becomes even more difficult and almost becomes a decision when we see that law enforcement officials from upstream to downstream are involved in a network of corruption that should be made enemies of law enforcement or targets of law enforcement itself.